Implicações filosóficas à formação no debate entre liberdade e responsabilidade - Schwarz, Altemir (My University, 2021)
The present study, entitled ?Philosophical implications for training in the debate between freedom and responsibility?, proposes to investigate in which aspects the thinking of Jean Paul Sartre and Emmanuel Levinas can contribute to the debate on formation. It is structured in three movements: the first movement searchs to position the formation's concept, with an emphasis on Paideia and Bildung; the second movement starts from the rupture of the metaphysical foundations, starting from subjectivity; the third movement presents the concepts of freedom and responsibility inserted in the discussion about the formation of subjectivity and proposes a formation from nothing, without guarantees, as a possibility. Theoretical in nature, the research is divided in four chapters: Chapter 1 deals with formation like Paideia, contributions of Aristóteles to the debate and formation like Bildung and Kant's contributions. Chapter 2 deals with subjectivity from the overcoming of metaphysical models and subject understanding, as well as the understanding of subjectivity from Sartre and Levinas. Chapter 3 deals with the thinking of Levinas and Sartre, with emphasis on the concepts of Freedom and Responsibility. Chapter 4 proposes an interpretation of the composition between four walls as a formative treaty and aims to forming as a possibility. [resumo fornecido pelo autor]
O presente trabalho, intitulado ?Implicações filosóficas à formação no debate entre liberdade e responsabilidade?, propõe-se a investigar em que aspectos o pensamento de Jean paul Sartre e Emmanuel Levinas pode contribuir para o debate sobre a formação. Estrutura-se em três movimentos: o primeiro movimento busca posicionar o conceito de formação, com ênfase na Paideia e na Bildung; o segundo movimento parte da ruptura com os fundamentos metafísicos, partindo da subjetividade; o terceiro movimento apresenta os conceitos de liberdade e responsabilidade inseridos na discussão acerca da formação da subjetividade e propõe uma formação a partir do nada, sem garantias, como possibilidade. De caráter teorético, a pesquisa está dividida em quatro capítulos: O capítulo 1 aborda a formação como Paideia, as contribuições de Aristóteles ao debate e a formação como Bildung e as contribuições de Kant. O capítulo 2 aborda a subjetividade a partir da superação dos modelos metafísicos e da compreensão de sujeito, bem como a compreensão de subjetividade a partir de Sartre e Levinas. O capítulo 3 ocupa-se do pensamento de Levinas e Sartre, com ênfase nos conceitos de Liberdade e Responsabilidade. O capítulo 4 propõe uma interpretação da obra entre quatro paredes como um tratado formativo e aponta a formação como possibilidade. [resumo fornecido pelo autor]
Keywords: Lévinas, Emmanuel, 1906-1995; Sartre, Jean-Paul, 1905-1980; Educação - Filosofia; Liberdade; Responsabilidade; Education - Philosophy; Liberty; Responsibility